The effect of an International competitive leaderboard on self-motivated simulation-based CPR practice among healthcare professionals: A randomized control trial. (May 2019) - Chang, Todd P.; Raymond, Tia; Dewan, Maya; MacKinnon, Ralph; Whitfill, Travis; Harwayne-Gidansky, Ilana; Doughty, Cara; Frisell, Karin; Kessler, David; Wolfe, Heather; Auerbach, Marc; Rutledge, Chrystal; et al.
Abstract: Background: Little is known about how best to motivate healthcare professionals to engage in frequent cardiopulmonary resuscitation (CPR) refresher skills practice. A competitive leaderboard for simulated CPR can encourage self-directed practice on a small scale. The study aimed to determine if a large-scale, multi-center leaderboard improved simulated CPR practice frequency and CPR performance among healthcare professionals. Methods: This was a multi-national, randomized cross-over study among 17 sites using a competitive online leaderboard to improve simulated practice frequency and CPR performance. All sites placed a Laerdal® ResusciAnne or ResusciBaby QCPR manikin in 1 or more clinical units – emergency department, ICU, etc. – in easy reach for 8 months. These simulators provide visual feedback during 2-minute compressions-only CPR and a performance score. Sites were randomly assigned to the intervention for the first 4-months or the second 4-months. Following any CPR practice by a healthcare professional, participants uploaded scores and an optional 'selfie' photo to the leaderboard. During the intervention phase, the leaderboard displayed ranked scores and high scores earned digital badges. The leaderboard did not display control phase participants. Outcomes included CPR practice frequency and mean compression score, using non-parametric statistics for analyses. Results: Nine-hundred nineteen participants completed 1850 simulated CPR episodes. Exposure to the leaderboard yielded 1.94 episodes per person compared to 2.14 during the control phase (p = 0.99). Mean CPR performance participants did not differ between phases: 90.7 vs. 89.3 (p = 0.19). Conclusion: A competitive leaderboard was not associated with an increase in self-directed simulated CPR practice or improved performance.